Hotspots and trends in key competencies on SDG: a visualized analysis based on citespace - Lu, Yanan; Musib, Ahmad Faudzi; Shi, Lin; Mohamed Razali, Camellia Siti Maya (Editora Alumni In, 2024)
Objective: Key competencies, regarded as essential elements in the development of curricula, have attracted considerable attentions in educational theory. To enhance comprehension of recent advancements, trending subjects, and research frontiers in the field of key competencies, this study collected related research and to provide a more distinct overview of the developmental patterns in key competencies. Methods: This study reviewed key competencies research from 2000 to 2022 using Scopus and CiteSpace for visualization and analysis. Annual publishing volume and country (region) distributions were analyzed. Key competencies fields, basic contents, and research hotspots were analyzed using keyword co-occurrence. Research frontiers and development trends were analyzed using high-frequency keywords. Results: The number of articles has steadily increased since 2005. The USA published the most, collaborating with Indonesia, the Netherlands, Russia, and India. Key competencies development and focus areas include “student”, “21st century skill”, “education”, “curriculum”, “learning”. Developmental trends in key competencies include “education”, “article”, “professional competence”, “problem solving”. Conclusion: The definition of key competencies and the content of curriculum reforms are attributed to variations in environments, cultures, and values among different international organizations and countries. Key competencies such as “communication”, “information technology”, “collaboration”, and “mother tongue” are prioritized in educational environments.